Emotional Expressions Reduce the Own-Age Bias - Cronin, Sophie; Craig, Belinda; Lipp, Ottmar (American Psychological Association, 2019)
© 2018 American Psychological Association. We are better at recognizing faces of our own age group compared to faces of other age groups. It has been suggested that this own-age bias (OAB) might occur because of perceptual-expertise and/or social- cognitive mechanisms. Although there is evidence to suggest effects of perceptual-expertise, little research has explored the role of social- cognitive factors. To do so, we looked at how the presence of an emotional expression on the face changes the magnitude of the OAB. Across 3 experiments, young adult participants were presented with young and older adult faces to remember. Neutral faces were first presented alone (Experiment 1) to validate the proposed paradigm and then presented along with angry (Experiment 2) and sad or happy faces (Experiment 3). The presence of an emotional expression improved the recognition of older adult faces, reducing the OAB which was evident for neutral faces. These results support the involvement of social- cognitive factors in the OAB, suggesting that a perceptual-expertise account cannot fully explain this face recognition bias.